Keteladanan Kepemimpinan Yosua dan Implikasinya terhadap Pelayanan Penatua di GKPPD Penjaraten Kabupaten Pakpak Bharat (Jurnal Pendidikan Agama dan Teologi, 2025)
This study aims to determine the exemplary leadership of Joshua and its implications for the ministry of the Elders at the GKPPD Penjaraten Resort Kuta Dame Pakpak Bharat. The background of this study departs from the fact that not all Elders demonstrate leadership character in accordance with Biblical values, especially as exemplified by Joshua as a humble, selfless, and exemplary leader of the Israelites. This study uses a qualitative method with a descriptive analysis approach, namely by analyzing and describing the character of Joshua's leadership and its relevance to the current condition of the Elders' ministry. The results of the study show four exemplary aspects of Joshua's leadership, namely: Joshua always prioritizes God, Joshua has great empathy for the Israelites, Joshua demonstrates obedience and steadfastness of faith, and Joshua implements servant leadership. Emulating Joshua's leadership is important for GKPPD Elders because Joshua demonstrates leadership that always prioritizes God in every decision. His exemplary in having empathy and concern for the congregation becomes a real example for Elders in serving the congregation with heart. Joshua's obedience and steadfast faith also encouraged the Elders to live with integrity and serve as spiritual role models. Furthermore, Joshua's selfless leadership style taught that true service is done with sincerity, not for personal gain.